FPGA based SVPWM controller for three phase AC-AC matrix converter - Duong, Hữu Trí; Nguyen, Văn Nhơ (Journal of Technical Education Science, 2010)
This paper presents a PWM control algorithm for three-phase AC-AC matrix converter with sinusoidal input/ output waveforms. The algorithm was based on technical space vector PWM (SVPWM) which achieved the maximum modulation ratio of 0.866 and unity input power factor. This technique is verified through simulation results using Matlab/Simulink software and experimental results using the Spartan 3E FPGA card with the four-step switching algorithm.